New Corporate Governance - Hilb, Martin (Springer, 2017)
Martin Hilb presents an innovative and integrated approach to the theory and practice of corporate governance. Central to this approach is a set of instruments - developed and tested by the author - that can be used by boards to offer effective strategic direction and control to their organizations. The board instruments can be readily applied to the targeted selection, review, remuneration and development of board members, and for conducting board self-evaluations. This new approach to corporate governance is based on four guiding principles: keep it situational, keep it strategic, keep it integrated, and keep it controlled. Together, these principles form the basis of an integrated approach that addresses all key aspects of corporate governance. The main arguments in each section are supported by conceptual models, practical board tools or case studies, making the book ideally suited to board members, senior managers and post-graduate students.